Assessing brain function in stressed healthy individuals following the use of a combination of green tea, Rhodiola, magnesium, and B vitamins: an fMRI study - Pickering, Gisèle; Noah, Lionel; Pereira, Bruno; Goubayon, Jonathan; Leray, Vincent; Touron, Ambre; Macian, Nicolas; Bernard, Lise; Dualé, Christian; Roux, Veronique; Chassain, Carine (Frontiers in Nutrition, 2023)
Introduction: This randomized, controlled, single-blinded trial assessed the effect of magnesium (Mg)-Teadiola (Mg, vitamins B6, B9, B12, Rhodiola, and green tea/L-theanine) versus placebo on the brain response to stressful thermal stimulus in chronically stressed, but otherwise healthy subjects. Impacts on stress-related quality-of-life parameters (depression, anxiety, sleep, and perception of pain) were also explored.The study recruited a total of 40 adults (20 per group), suffering from stress for more than 1 month and scaling ≥14 points on the Depression Anxiety Stress Scale (DASS)-42 questionnaire at the time of inclusion. Individuals received oral Mg-Teadiola or placebo for 28 days (D). fMRI analysis was used to visualize the interplay between stress and pain cerebral matrices, using thermal stress model, at baseline (D0) and afterD28.: Based on blood-oxygen-level-dependent (BOLD) signal variations during the stress stimulation (before pain perception), a significantly increased activation between D0 and D28 was observed for left and right frontal area [p = 0.001 and p = 0.002, respectively], left and right anterior cingulate cortex (ACC) [p = 0.035 and p = 0.04, respectively], and left and right insula [p = 0.034 and p = 0.0402, respectively] in Mg-Teadiola versus placebo group. During thermal pain stimulation, a significantly diminished activation of the pain matrix was observed between D0 and D28, for left and right prefrontal area [both p = 0.001], left and right insula [p = 0.008 and p = 0.019, respectively], and left and right ventral striatum [both p = 0.001] was observed in Mg-Teadiola versus placebo group. These results reinforce the clinical observations, showing a perceived benefit of Mg-Teadiola on several parameters. After 1 month of treatment, DASS-42 stress score significantly decreased in Mg-Teadiola group (effect size [ES] −0.46 [−0.91; −0.01], p = 0.048). Similar reductions were observed on D14 (p = 0.011) and D56 (p = 0.008). Sensitivity to cold also improved from D0 to D28 for Mg-Teadiola versus placebo (ES 0.47 [0.02; 0.92] p = 0.042).Supplementation with Mg-Teadiola reduced stress on D28 in chronically stressed but otherwise healthy individuals and modulated the stress and pain cerebral matrices during stressful thermal stimulus.